New Zealand's extinct giant raptor (Hieraaetus moorei) killed like an eagle, ate like a condor. Issue 1964 (8th December 2021) - van Heteren, A. H.; Wroe, S.; Tsang, L. R.; Mitchell, D. R.; Ross, P.; Ledogar, J. A.; Attard, M. R. G.; Sustaita, D.; Clausen, P.; Scofield, R. P.; Sansalone, G.
Abstract : The extinct Haast's eagle or harpagornis ( Hieraaetus moorei ) is the largest known eagle. Historically, it was first considered a predator, then a scavenger, but most recent authors have favoured an active hunting ecology. However, the veracity of proposed similarities to carrion feeders has not been thoroughly tested. To infer feeding capability and behaviour in harpagornis, we used geometric morphometric and finite-element analyses to assess the shape and biomechanical strength of its neurocranium, beak and talons in comparison to five extant scavenging and predatory birds. The neurocranium of harpagornis is vulture-like in shape whereas its beak is eagle-like. The mechanical performance of harpagornis is closer to extant eagles under biting loads but is closest to the Andean condor ( Vultur gryphus ) under extrinsic loads simulating prey capture and killing. The talons, however, are eagle-like and even for a bird of its size, able to withstand extremely high loads. Results are consistent with the proposition that, unlike living eagles, harpagornis habitually killed prey larger than itself, then applied feeding methods typical of vultures to feed on the large carcasses. Decoupling of the relationship between neurocranium and beak shape may have been linked to rapid evolution.